CALCULATION OF WAVE EFFECTS IN THE CONDITIONS OF INTERACTION OF WAVES AND CURRENTS - Eshev, Sobir; Latipov, Shakhboz; Rakhimov, Ashraf; Kuvvatov, Zhobir; Yuldosheva , Umida (Innovatsion texnologiyalar, 2023)
The article deals with the generation of wind waves for the conditions of large earthen channels, in which the generation of wind waves is significantly affected by a stationary flow and a limited width of a water body. Dependences for determining the height and periods of waves are obtained.